Unfocused written corrective feedback for academic discourse: the sociomaterial potential for writing development and socialization in higher education - Daron Benjamin Loo (National Research University Higher School of Economics, 2022)
Background. There is a prevailing belief that unfocused written corrective feedback may not be suitable to promote students’ academic writing development. Purpose. This perspective piece demonstrates how unfocused written corrective feedback reflects the principles of sociomateriality, which views learning as dynamic. Perspectives. Unfocused written corrective feedback has the potential to support university students’ academic discourse socialization. This perspective is based on the observation that actual written corrective feedback in a classroom setting is varied and contextual, and not focused on any particular grammar form or writing feature. Conclusion. Unfocused written corrective feedback represents an optimal approach to support university students’ awareness and engagement with variables found in their learning ecology. These variables can support students’ academic writing development.